Advances in Biochar-Based Materials for Environmental Remediation: Mechanisms, Applications, and Future Perspectives - Liu, Yaning; Li, Jingxin; Lei, Shengyan; Chen, Min; Nong, Xiuzhen (International Journal of Materials Science and Technology Studies, 2025)
Biochar-based materials have emerged as a promising solution for addressing multiple environmental challenges through sustainable biomass utilization. Derived from agricultural and forestry waste via pyrolysis and hydrothermal carbonization, these carbon-rich substances exhibit exceptional adsorption capabilities due to their porous architecture and abundant surface functional groups. Recent advancements in modification techniques, particularly chemical activation and nanomaterial integration, have substantially enhanced their pollutant removal efficiency and structural stability. Practical applications demonstrate remarkable effectiveness in immobilizing heavy metal contaminants, degrading persistent organic pollutants, and restoring degraded soils through improved nutrient retention and microbial activity enhancement. The materials’ dual functionality in carbon sequestration and waste valorization presents a cost-effective strategy for mitigating climate change impacts. However, scalability challenges persist in optimizing production parameters for diverse feedstock types while maintaining consistent quality. Long-term ecological impacts require thorough investigation regarding potential secondary contamination risks and soil ecosystem interactions. Future research directions should prioritize developing standardized characterization protocols, intelligent responsive materials for targeted remediation, and synergistic systems combining biochar with phytoremediation technologies. This comprehensive analysis underscores the need for interdisciplinary collaboration to bridge laboratory innovations with practical environmental engineering applications, ultimately contributing to sustainable circular economy models in ecological restoration.